'Relive the passion, find your affair': Revising the infidelity script online. (December 2019) - Harrison, Katherine
Affairs websites such as Victoria Milan, Gleeden or Illicit Encounters are the latest in a long line of commercial online ventures offering different kinds of intimacy. While online dating sites have long been used as a covert way to find additional partners or extramarital intimacy, recent years have seen an increase in the variety of new media services explicitly targeted at unfaithful partners. However, as the July 2015 hacking (and subsequent media coverage) of well-known affairs site, Ashley Madison, showed, the status of these sites is still contested and the services they offer still highly provocative. With this in mind, this article explores the intersection of new media and the contested form of intimacy often referred to as 'infidelity'. In this article, I analyse material from four websites offering non-consensual non-monogamies to examine how they are attempting to change the cultural script of infidelity through a combination of content and material affordances. To do so, I draw on the idea of intimacy as a kind of organizing 'public' narrative that determines 'private' acts of intimacy (Berlant, 2000).